(untitled) (The Review of Diabetic Studies, 2024)
Background Classification frameworks such as ICD, ICPC, and SNOMED play a fundamental role in standardizing clinical documentation and improving workflow processes in primary care. Despite the increasing adoption of these systems, limited evidence exists regarding the contributions of support professionals—particularly nursing staff and dental assistants—in sustaining classification-driven workflows within Family Medicine. Objective This study examines the impact of classification-based approaches on organizational performance in Family Medicine settings and evaluates the roles of key support professionals in enhancing documentation accuracy, workflow efficiency, and interprofessional coordination. Methods A mixed-methods design was used, combining quantitative data (surveys, workflow metrics, documentation audits) with qualitative data (semi-structured interviews, thematic analysis). Findings were triangulated with evidence from published studies between 2000 and 2024. Classification systems assessed included ICD, ICPC, and SNOMED. Results Classification-driven approaches were associated with significant improvements in documentation completeness, coding accuracy, referral processing speed, and data retrieval efficiency. Nursing staff played a central role in triage classification, chronic-disease documentation, and referral coding, while dental assistants contributed to oral-health documentation and preventive-care classification in integrated Family Medicine models. Barriers included insufficient training, system complexity, and workload pressures, whereas facilitators included continuous training, administrative support, clear coding guidelines, and digital tools. These findings aligned strongly with existing literature (Okkes et al., 2002; Gusso & McGough, 2020; Aiken et al., 2017). Conclusion Classification-driven processes enhance accuracy, efficiency, and organizational coherence in Family Medicine. The active engagement of support professionals—especially nursing staff and dental assistants—is essential to sustaining high-quality classification practices. Strengthening training programs, optimizing EHR integration, and reinforcing administrative support are critical for maximizing classification effectiveness and improving care continuity.